1992
DOI: 10.1093/infdis/166.6.1346
|View full text |Cite
|
Sign up to set email alerts
|

The Spread of Multiply Resistant Streptococcus pneumoniae at a Day Care Center in Ohio

Abstract: Streptococcus pneumoniae, type 23F, resistant to penicillin (MIC, 2 micrograms/mL) and multiple other antimicrobic agents, was isolated from middle ear fluid of a child with otitis media attending a day care center in Ohio. To determine the extent of spread of this strain, nasopharyngeal culture surveys were done, and 52 carriers were identified among 250 children attending the index day care center. No carriers were found among 121 children at two other day care centers in the same urban area. Use of prophyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
150
4
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(160 citation statements)
references
References 44 publications
4
150
4
2
Order By: Relevance
“…[1][2][3] Studies of the epidemiology of PRSP have consistently identified a strong association between prior antibiotic use and the risk of acquiring PRSP. 1,[4][5][6] In light of these findings, the Centers for Disease Control and Prevention and other authorities have intensified their recommendations and efforts to promote judicious antibiotic use. [7][8][9][10] A recent study of physician practice patterns in the United States identified bronchitis as an important target for reducing unnecessary antibiotic use in ambulatory practice.…”
Section: T He Rapidly Rising Prevalence Of Penicillin-resistantmentioning
confidence: 99%
“…[1][2][3] Studies of the epidemiology of PRSP have consistently identified a strong association between prior antibiotic use and the risk of acquiring PRSP. 1,[4][5][6] In light of these findings, the Centers for Disease Control and Prevention and other authorities have intensified their recommendations and efforts to promote judicious antibiotic use. [7][8][9][10] A recent study of physician practice patterns in the United States identified bronchitis as an important target for reducing unnecessary antibiotic use in ambulatory practice.…”
Section: T He Rapidly Rising Prevalence Of Penicillin-resistantmentioning
confidence: 99%
“…Although the US, along with many other developed nations, is facing a large-scale problem with antibiotic resistant bacteria (Baquero, Baquero-Artigao, Canton, & Garcia-Rey, 2002;McCaig & Hughes, 1995;Neu, 1992;Reichler et al, 1992;Schwartz, 1999; Whitney et al, 2000;Wise et al, 1998), inappropriate prescribing of antibiotics for viral infections is common (Finkelstein et al, 2000;Gonzales, Malone, Maselli, & Sande, 2001;Gonzalez, Steiner, & Sande, 1997;Mainous, Hueston, & Clark, 1996;Mangione-Smith et al, in press;McCaig, Besser, & Hughes, 2002;Pennie, 1998). Inappropriate use of antibiotics has led to rapidly increasing risks of resistance among many strains of bacteria that commonly infect children and adults (Cristino, 1999;Deeks et al, 1999;Gomez et al, 1995;Nava et al, 1994;Watanabe et al, 2000).…”
mentioning
confidence: 99%
“…The presence of multiply-resistant pneumococcal strains among children at a DCC and in household members and members of the surrounding community is of substantial importance because of the potential of these strains to cause invasive disease. 6,[9][10][11][12][13][14][15][16] This study also demonstrates that the risk of carrying multiply-resistant strains of pneumococci is directly related to the administration of antimicrobial therapy in the preceding three to four months. In settings in which a strain is resistant to multiple antimicrobial agents, prevalent antibiotic therapy can result in increased risk of carriage of the drug-resistant strain.…”
Section: Discussionmentioning
confidence: 55%
“…Our findings supports earlier studies from similar centers over the last decade. [9][10][11][12][13][14][15][16][17][18][19][20][21] Recent research established daycare attendance as an important factor influencing the epidemiology of many infectious diseases. [26][27][28] A number of studies have demonstrated a strong association between daycare attendance and increased carriage of S. pneumoniae, especially of resistant strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation